2015
DOI: 10.1108/ijssp-12-2013-0116
|View full text |Cite
|
Sign up to set email alerts
|

Active labour market policy and its outcomes

Abstract: Purpose -The purpose of this paper is to examine the effect of workfare programme participation on self-efficacy, because many studies suggest that sufficient self-efficacy is essential for successful job search in modern labour markets. Design/methodology/approach -The paper analyses an exemplary German workfare programme' the so-called "One-Euro-Jobs" programme and examines whether participation in this programme improved the self-efficacy of participants. The analyses are based on survey data (Panel Study L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The study results show that community service does not increase self-reported mental health and decreases mental complaints. The absence of change in mental health is consistent with Tisch and Wolff's (2015) findings how community service is not associated with selfefficacy. However, other research found that participants' life satisfaction and affective well-being are higher during community service and explained by its temporary and voluntary nature (Knabe et al, 2017).…”
Section: Discussion and Application To Practicesupporting
confidence: 88%
See 2 more Smart Citations
“…The study results show that community service does not increase self-reported mental health and decreases mental complaints. The absence of change in mental health is consistent with Tisch and Wolff's (2015) findings how community service is not associated with selfefficacy. However, other research found that participants' life satisfaction and affective well-being are higher during community service and explained by its temporary and voluntary nature (Knabe et al, 2017).…”
Section: Discussion and Application To Practicesupporting
confidence: 88%
“…It would be worth further exploration to see whether changes in mental health require more extensive participation in community service or intensive and multicomponent support. Previous findings show efficient employment policy interventions include nondegrading activities, enhancing employability skills, and increasing employment opportunities (Strandh, 2001;Wulfgramm, 2011;Tisch & Wolff, 2015). To understand the underlying mechanisms under which latent benefits of work get strengthened, we recommend that further research delineate several specific intervention groups and explore clients' experiences during community service.…”
Section: Discussion and Application To Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Also focusing on professionals' role in developing clients' self-efficacy, Blankertz et al (2004) present a model that focuses on developing self-efficacy through the alliance between counsellor and patient. While other studies have indicated positive (Creed, Bloxsome, and Johnston 2001) as well as non-significant (Tisch and Wolf 2015) effects of specific programmes on clients' self-efficacy, the research of both Blankertz et al (2004) and McDonald and Marston (2008) indicates the importance of the interaction with individual professionals for supporting and developing self-efficacy.…”
Section: Self-efficacy and Unemploymentmentioning
confidence: 75%
“…From this point of view, several studies have shown the existence of a relationship between participation in activation programmes and the creation of new social ties (Anderson, 2009). Other scholars have analysed the relations among labour market policies and life satisfaction (Wulfgramm, 2014), well-being (Sage, 2014), self-efficacy (Tisch and Wolff, 2015), and social marginalisation (Breidahl and Clement, 2010). The relations can depend on various factors, such as different types of activation regimes and activation interventions (Carter and Whitworth, 2016).…”
Section: Activation Policies In Europe and In Italymentioning
confidence: 99%